Digital habits of pulmonary rehabilitation service-users following the COVID-19 pandemic. (4th January 2022) - Polgar, Oliver; Patel, Suhani; Walsh, Jessica A; Barker, Ruth E; Ingram, Karen A; Kon, Samantha SC; Man, William DC; Nolan, Claire M
Objective: We previously demonstrated low levels of digital literacy amongst pulmonary rehabilitation service-users prior to the COVID-19 pandemic. We aimed to identify whether the pandemic accelerated digital literacy in this population, resulting in greater acceptance of remote web-based pulmonary rehabilitation programme models. Methods: We surveyed digital access and behaviours and pulmonary rehabilitation delivery preferences of service-users referred to pulmonary rehabilitation in 2021 (cohort 2021) and propensity score-matched them to a cohort who completed the survey in 2020 (cohort 2020). Results: There were indicators that digital access and confidence were better amongst the Cohort 2021 but no difference was seen in the proportion of patients choosing remote web-based pulmonary rehabilitation as an acceptable method of receiving pulmonary rehabilitation. Conclusion: In an unselected cohort of service-users, remote web-based pulmonary rehabilitation was considered acceptable in only a minority of patients which has implications on healthcare commissioning and delivery of pulmonary rehabilitation.